2015
DOI: 10.1002/2015gl063802
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic rupture models of earthquakes on the Bartlett Springs Fault, Northern California

Abstract: The Bartlett Springs Fault (BSF), the easternmost branch of the northern San Andreas Fault system, creeps along much of its length. Geodetic data for the BSF are sparse, and surface creep rates are generally poorly constrained. The two existing geodetic slip rate inversions resolve at least one locked patch within the creeping zones. We use the 3‐D finite element code FaultMod to conduct dynamic rupture models based on both geodetic inversions, in order to determine the ability of rupture to propagate into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Dynamic rupture simulations show that the viability of a partially creeping fault segment for throughgoing fault rupture depends to some extent on the relative downdip widths of locked and creeping zones on a fault (Lozos, 2013;Lozos et al, 2015). Dynamic rupture simulations show that the viability of a partially creeping fault segment for throughgoing fault rupture depends to some extent on the relative downdip widths of locked and creeping zones on a fault (Lozos, 2013;Lozos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic rupture simulations show that the viability of a partially creeping fault segment for throughgoing fault rupture depends to some extent on the relative downdip widths of locked and creeping zones on a fault (Lozos, 2013;Lozos et al, 2015). Dynamic rupture simulations show that the viability of a partially creeping fault segment for throughgoing fault rupture depends to some extent on the relative downdip widths of locked and creeping zones on a fault (Lozos, 2013;Lozos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The confirmed presence of surface creep on the northern Rodgers Creek fault, extending northwestward from Santa Rosa, has implications for seismic hazard assessment. Dynamic rupture modeling experiments targeted at similar, neighboring structures such as the Bartlett Springs fault, have shown that creeping areas can channel fault ruptures at depth or arrest them completely [e.g., Lozos et al , ]. This would likely reduce the expected strong shaking, although detailed scenario modeling of the Rodgers Creek fault would be required to quantify precisely by how much.…”
Section: Discussionmentioning
confidence: 99%
“…Lozos et al . [] also adopted this method to simulate spontaneous earthquake rupture propagation at locations throughout a fault's depth that are inferred to creep interseismically. This strategy effectively slowed or stopped the simulated earthquake rupture as it encountered the creeping portions of the fault surface, both along strike and along dip.…”
Section: Strong Shaking Due To Earthquakes On Creeping Faultsmentioning
confidence: 99%
“…Quin [1990], who conducted 3-D spontaneous rupture simulations that incorporated a critical stress failure criterion [Das and Kostrov, 1983], and Harris and Day [1999], who conducted 3-D spontaneous rupture simulations that incorporated a slipweakening failure criterion [Ida, 1972;Palmer and Rice, 1973], both used zero or negative initial stress drop on the upper portions of fault surfaces near the Earth's surface, as a proxy for velocity-strengthening friction behavior, and to slow the earthquake rupture on its way up to the Earth's surface. Lozos et al [2015] also adopted this method to simulate spontaneous earthquake rupture propagation at locations throughout a fault's depth that are inferred to creep interseismically. This strategy effectively slowed or stopped the simulated earthquake rupture as it encountered the creeping portions of the fault surface, both along strike and along dip.…”
Section: 1002/2016rg000539mentioning
confidence: 99%